Social Assistance and Mental Health: Evidence from Longitudinal Data on Pharmaceutical Consumption - Margareta Dackehag; Lina Maria Ellegård; Ulf-G. Gerdtham; Therese Nilsson (Lund University, School of Economics and Management, Department of Economics, 2018)
This paper examines the short-term effect between take-up of Social Assistance Benefit (SAB) and mental health. Using a panel dataset including rich yearly register data on e.g. income, income sources, unemployment and types of pharmaceutical consumption for over 140,000 Swedes 2006-2012, we quantify the importance of the psychosocial dimensions (e.g. shame and guilt) of the socioeconomic status – mental health nexus. Our main independent variable is an indicator for SAB, which is the means-tested last-resort option for individuals with no other means to cover necessary living expenses, received by six per cent of all Swedish households annually. Mental ill-health is measured by data on prescribed antidepressants, anxiolytics, or hypnotics. While SAB strongly associates with psychopharmaca consumption in a cross-section of observations, the association largely disappear once we introduce individual fixed effects. These results indicate that other mechanisms than shame or guilt related to the SAB experience are more important for mental health in the short term.
Additional information: Additional online appendix available.
Keywords: I12; I14; I18; 330; mental health; socio-economic status; social assistance; shame; guilt; individual fixed effect